2020
DOI: 10.2147/ijn.s229154
|View full text |Cite
|
Sign up to set email alerts
|

<p>Doxorubicin-Loaded Carbon Dots Lipid-Coated Calcium Phosphate Nanoparticles for Visual Targeted Delivery and Therapy of Tumor</p>

Abstract: Background: Carbon dots (CDs) have attracted extensive attention in recent years because of their high biocompatibility and unique optical property. But they could not be well applied in the drug delivery system to enable distribution in tumor sites with their low pH sensitivity. They are barriers for drug delivery. CDs as an imaging proper were conjugated with doxorubicin (DOX) lipid-coated calcium phosphate (LCP) nanoparticle, for a pH-sensitive nanocarrier and delivery of the antitumor drugs. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…23 The study by Yang et al showed the nuclear delivery of DOX using nuclear targeting aptamer moiety functionalized carbon dots, 20 and Hailing et al used the PEI polymer to achieve the same. 24 Except for a few studies conducted in the in vivo environment 17,19,24–26 and our study using fluorescence lifetime imaging (FLIM), 27 most of the studies ignore the effect of the protein corona.…”
Section: Introductionmentioning
confidence: 99%
“…23 The study by Yang et al showed the nuclear delivery of DOX using nuclear targeting aptamer moiety functionalized carbon dots, 20 and Hailing et al used the PEI polymer to achieve the same. 24 Except for a few studies conducted in the in vivo environment 17,19,24–26 and our study using fluorescence lifetime imaging (FLIM), 27 most of the studies ignore the effect of the protein corona.…”
Section: Introductionmentioning
confidence: 99%
“…38 Due to their small structure, CQDs can be trapped in tumour sites by an enhanced permeability and retention effect (EPR). 39,40 In normal tissues, the microvascular endothelial space is dense and intact, and CQDs are difficult to penetrate the vascular wall, while in solid tumor tissues, blood vessels are abundant, and the wide vascular wall space, poor structural integrity and missing lymphatic return result in high selective permeability and retention of large CQDs. 41,42 Therefore, EPR effect promotes the selective distribution of CQDs in tumor tissues, which can increase antitumour efficacy and reduce systemic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, a large number of nano-and submicron-sized delivery systems for anti-cancer drugs have been developed [3]. The basic structure of carriers may vary; bio-organic objects are commonly used as carriers: exosomes [4], liposomes [5], dendrimers, macrophages [6], micelles [7], as well as inorganic substances, e.g., carbon nanotubes [8], calcium phosphates [9,10], SiO 2 [11], and CaCO 3 [12]. It should be noted that manufacturing of most DS is rather laborious; in a number of cases, it is necessary to synthesize complex polymers.…”
Section: Introductionmentioning
confidence: 99%